A multifunctional basic pH indicator probe for distinguishable detection of Co2+, Cu2+ and Zn2+ with its utility in mitotracking and monitoring cytoplasmic viscosity in apoptotic cells. Issue 17 (21st April 2022) - Yadav, Pranjalee; Gond, Sarita; Shekher, Anusmita; Gupta, Subash Chandra; Singh, Udai P.; Singh, Vinod P.
Abstract : A single multifunctional probe for discriminating sensing and bioimaging applications has been synthesized and characterized via a single crystal XRD technique. Abstract : Metal ions such as Co 2+, Cu 2+ and Zn 2+ have extensive applications in biological and industrial realms, but the toxicity caused by these ions poses a serious threat to mankind. However, there is no report in the literature on the development of a chemosensor for distinguishable detection of these toxic ions. Addressing this challenge, a multifunctional probe as a basic pH indicator with both colorimetric and fluorescence turn-on responses has been reported. The probe selectively discriminates Co 2+, Cu 2+ and Zn 2+ ions with brown, dark yellow and greenish yellow colors, respectively, in DMF : water (9 : 1 v/v, HEPES 10 mM). Additionally, a fluorescence turn-on response specific to Zn 2+ has also been observed. The sensing mechanism has been explored using UV-Vis, fluorescence spectroscopy and 1 H NMR titration and confirmed with computational results. The inhibition of CN isomerization and excited state intramolecular proton transfer (ESIPT) along with chelation enhanced fluorescence emission (CHEF) result in fluorescence enhancement with Zn 2+ . Job's plot and HRMS spectra confirm a 1 : 1 (L : M) stoichiometry between the probe and metal ions. The probe is able to exhibit excellent viscochromism in DMF : glycerol medium. Live cell imaging on SiHa cells has been successfully performed for intra-cellular detection of Zn 2+ at basic pH. Furthermore, the probe displays its utility in mitotracking and monitoring cytoplasmic viscosity changes in SiHa cells. It is efficiently used to recognize the apoptosis process by displaying an enhancement in fluorescence intensity from cancerous SiHa cells to apoptotic cells.